Globalization and Religion: The Case of Malacca and the Work of Robert Morrison - Wu, Ziming (Religions, 2012)
Religion has long been a significant factor in the process of globalization. In this article, the author attempts to explore and review religious factors involved in the history of Malacca (Melaka) and in the missionary work of Robert Morrison in the early 19th century. Malacca has long been a meeting place for various religions in their respective processes of globalization. Robert Morrison was the first Protestant Missionary to come to the Chinese Mainland. He arrived in 1807. However, after 10 years of working in Canton and Macau, he made a proposal for setting up a mission school in Malacca, hence the Anglo-Chinese College of 1818. It was found that, indeed, Morrison had learned much from his experiences in China and in Malacca, especially in paying due respect to Chinese culture.